FEATURES AND ADVANTAGES OF E-TEXTBOOKS IN THE EDUCATION SYSTEM - Kadirova Shokhibonu Muhammadovna (Journals Park Publishing, 2022)
This article provides a reference on the changes in the training system and the work carried out on them. The main essence of the article is this.
Keywords: block; concept; elements